Guided internet-based transdiagnostic individually tailored Cognitive Behavioral Therapy for symptoms of depression and/or anxiety in college students: A randomized controlled trial. (March 2022) - Karyotaki, Eirini; Klein, Anke M.; Ciharova, Marketa; Bolinski, Felix; Krijnen, Lisa; de Koning, Lisa; de Wit, Leonore; van der Heijde, Claudia M.; Ebert, David D.; Riper, Heleen; Batelaan, Neeltje; Vonk, Peter; et al.
Abstract: Common mental disorders, such as depression and anxiety, often emerge in college students during the transition into early adulthood. Mental health problems can seriously impact students' functioning, interpersonal relationships, and academic achievement. Actively reaching out to college students with mental health problems and offering them internet-based interventions may be a promising way of providing low-threshold access to evidence-based treatment in colleges. This randomized controlled trial aimed to assess the effectiveness of a guided web-based transdiagnostic individually tailored Cognitive Behavioral Therapy (iCBT) in treating college students with depression and/or anxiety symptoms. Through an online survey that screened college students' mental health, we recruited 100 college students aged ≥18 years who reported mild to moderate depression and/or anxiety symptoms and were attending colleges in the Netherlands. Participants were randomly allocated to guided iCBT (n = 48) or treatment as usual (TAU) control (n = 52). Primary outcomes were symptoms of depression and anxiety measured at post-treatment (7 weeks post-randomization). We also measured all outcomes at 6- and 12-months post-randomization. All analyses were based on the intention-to-treat principle and were repeated using the complete-case sample. We found no evidence of a difference between the effects of guided iCBT and TAU in any of the examined outcomes (i.e., symptoms of depression and anxiety, quality of life, educational achievement, and college dropout) across all time points (p > .05). There was no evidence that effects of iCBT were associated with treatment satisfaction and adherence. More research into transdiagnostic individually tailored iCBT is necessary. Further, future studies should recruit larger samples to investigate possible smaller but clinically relevant effects of internet-based interventions for college students with depression and/or anxiety. Highlights: Depression and anxiety impose a considerable burden on college students and society. Colleges can use digital innovations to provide early interventions in colleges. iCBT did not lead to improvements on depression/anxiety in college students. More research is needed on the effects of iCBT in college students.